2012
DOI: 10.1093/erae/jbs021
|View full text |Cite
|
Sign up to set email alerts
|

Experimental auctions, collective induction and choice shift: willingness-to-pay for rice quality in Senegal

Abstract: We propose a collective induction treatment as an aggregator of information and preferences, which enables testing whether consumer preferences for food quality elicited through experimental auctions are robust to aggregation. We develop a two-stage estimation method based on social judgment scheme theory to identify the determinants of social influence in collective induction. Our method is tested in a market experiment aiming to assess consumers' willingness-to-pay for rice quality in Senegal. No significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
2
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 60 publications
7
55
2
8
Order By: Relevance
“…Second, indifference is more likely to occur in the morning sessions, while participation in the afternoon increases the likelihood to choose FBR. While several auction studies with staple crops reported higher WTP values in the morning (42,43,73,74) , which is likely due to hunger and increased interest in buying and consuming food, the present study reports a somewhat similar time-ofthe-day effect that refers to product choice. Respondents in the morning are more favourable to all folate products, rather than preferring one.…”
Section: Determinants Of Product Choicesupporting
confidence: 54%
See 2 more Smart Citations
“…Second, indifference is more likely to occur in the morning sessions, while participation in the afternoon increases the likelihood to choose FBR. While several auction studies with staple crops reported higher WTP values in the morning (42,43,73,74) , which is likely due to hunger and increased interest in buying and consuming food, the present study reports a somewhat similar time-ofthe-day effect that refers to product choice. Respondents in the morning are more favourable to all folate products, rather than preferring one.…”
Section: Determinants Of Product Choicesupporting
confidence: 54%
“…Hence, we address the need to include substitutes in GM food auctions (35)(36)(37) . Such a multiple-product auction design is often applied to simultaneously determine consumers' WTP for different food products (38)(39)(40)(41) , including rice (42,43) , GM foods (44)(45)(46) and biofortified crops (47) . While FAR is currently not sold at the marketplace, FBR is still in a development phase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggest that the premium estimations are not driven by these factors. Although we have shown that the social interaction effect can be eliminated when the difference in WTP is modeled, a more robust approach of collective induction based on social judgment theory can be built into the design of future experimental auctions to rigorously identify the social interaction effect (Demont et al 2013). An examination of the effects of hypothetical bias or participants' inability to make an out-of-pocket payment after "winning" in the experiment is a significant part of this analysis.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Half of the sessions were conducted at 12 pm and half of the sessions were conducted at 1 pm. We only allowed a one hour difference between scheduled sessions to minimize potential "time of the day" effects on bidding behavior (Demont et al, 2012(Demont et al, , 2013Hoffman et al, 1993;Menkhaus et al, 1992;Morawetz et al, 2011). Since we could not fully control subjects' eating behavior before participating in the auction, we also asked subjects to self-report their hunger level.…”
Section: Methodsmentioning
confidence: 99%